Characteristics of the Functional Properties of Pepetek Fish Protein Isolate (Leiognathus sp.) with different pH treatments - Siwi, Fiendy Sutan; Haryati, Sakinah; Aditia, Rifki Prayoga (Universitas Teuku Umar, 2025)
Common ponyfish (Leiognathus sp.) is a low-economic fish in Banten waters and is widely landed at the Nusantara Fisheries Port (PPN) Karangantu, Banten, with a production of 206.7 tonnes per year. Pepetek fish has a high protein content of 19.66%, so it has the potential as a raw material for making fish protein isolate. This study aims to determine the optimal protein solubility, pH, and characterisation of pepetek fish protein isolate as a food ingredient. The method of making pepetek fish isolate in this study was by performing a pH shift, which can effectively maintain fish meat protein. This study involved four treatment levels of protein solubility pH, specifically pH 10, pH 11, and pH 12, each with two replications. The research data was analysed using SPSS V29. All research data, including yield, pH value, proximate test, and protein functional properties, were analysed using ANOVA; if they were significantly different, Duncan's further test was carried out. The best protein isolate preparation of pepetek fish with different pH methods was at a protein solubility pH of pH 11. The resulting characteristics were a yield of 12.98%. The protein isolate from pepetek fish exhibits several physical characteristics related to its functional properties, including a Kamba density of 1.15 g/mL, 2.5% gel formation, an emulsion capacity of 1.31 g/mL, low emulsion stability, a foam capacity of 0.41 g/mL, a water absorption capacity of 2.74 g/mL, an oil absorption capacity of 2.79 g/mL, a water holding capacity (WHC) of 0.55 g/mL (55%), and solubility of 0.33 g/mL. The chemical characteristics of the protein isolate include a water content of 11.17% (bb), an ash content of 13.5% (bk), a fat content of 13.78% (bk), and a protein content of 72.64% (bk). The protein isolate produced by pepetek fish can be used as a food ingredient.